MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RPP KURIKULUM 2013 MELALUI KEGIATAN IHT (IN HOUSE TRAINING) DI SD NEGERI MANGGALAI KECAMATAN TINANGKUNG BANGGAI KEPULAUAN SEMESTER GANJIL TAHUN PELAJARAN 2021/2022: SD NEGERI MANGGALAI KECAMATAN TINANGKUNG BANGGAI KEPULAUAN - ADENAN LUANDE (Mitra Pendidikan, 2022)
The teacher's role in transforming educational inputs is very important. This is inseparable from the existence of a school system that includes input - process - output, where the teacher as one of the input factors plays an important role in the process to be able to produce output in accordance with what is expected. Learning planning which includes activities to review the curriculum, compile a syllabus, learning strategies, learning resources used and units of learning activities is actually the most important thing because planning is the basis of the implementation carried out. However, this is often overlooked because many teachers think that lesson planning can be done by copying documents prepared by other schools. This has an impact on the number of plans that are not in accordance with the needs of the school. the average implementation of In House Training in the preparation of lesson plans in accordance with the 2013 curriculum obtained an average score of 82 or 82% spread and is included in good criteria (B).